SISTEM INFORMASI HASIL PANEN PADI KABUPATEN SUBANG BERBASIS WEB - Ade Supriatna (Jurnal Teknologi Informasi dan Komunikasi, 2020)
Rice production and productivity in Subang district must be easily informed by the Department of Agriculture in accordance with advances in information technology and the internet. This study is about data and information that is integrated into a computer-based information system related to the yield of rice crops. The computer-based rice yield report is intended to make it easier to enter data sourced from the corm area online. Then from the user (community) side it will be more practical and easier to get information. And services at the subang agriculture service do not always have to be directly in the office but can be done online. That way the reporting process, fast and structured.Reporting, which was originally still manual, was to recapitulate paper-based transactions and then switch to the application of web-based computer technology and the research method was quantitative.